2017
DOI: 10.1111/jdv.14740
|View full text |Cite
|
Sign up to set email alerts
|

Skin cancer prevention campaign in childhood: survey based on 3676 children in Brazil

Abstract: Educative sun exposure programmes in childhood are a relevant tool to modify the history of life for next generations, to concern the skin cancer and good health practices.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
4
0
1

Year Published

2021
2021
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(6 citation statements)
references
References 22 publications
1
4
0
1
Order By: Relevance
“…In previous analyses, we revealed that caregivers’ self-perception as a role model is also associated with use of sun protection measures in the child [ 11 ]. This supports the assumption that the caregivers’ attitude as well as their own sun protection behaviors are important for children’s behavior [ 21 , 41 , 42 , 43 ] and deserve particular attention in future prevention campaigns [ 11 ].…”
Section: Discussionsupporting
confidence: 78%
“…In previous analyses, we revealed that caregivers’ self-perception as a role model is also associated with use of sun protection measures in the child [ 11 ]. This supports the assumption that the caregivers’ attitude as well as their own sun protection behaviors are important for children’s behavior [ 21 , 41 , 42 , 43 ] and deserve particular attention in future prevention campaigns [ 11 ].…”
Section: Discussionsupporting
confidence: 78%
“…Fourth, especially young children cannot protect themselves and thus depend on their parents [11], who therefore play an important role for sun protection during childhood. Moreover, parents can act as a role model for their children not only with their attitudes towards sun protection but especially with their own sun protection behavior [12][13][14][15].…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies exploring sun protective practices of children have mostly reported a positive association with younger age [11,[16][17][18][19] and sensitive fair skin [18][19][20], while mixed results are found for parents' age [15,16] and children's sex [18][19][20]. Although studies on sun protective guidance for children exist, it is often difficult to draw conclusions for nationwide prevention campaigns that target parents because studies have often been conducted in kindergarten [16,21], preschool [20], or school settings [13]. In addition, many studies have been conducted outside Europe [13][14][15]17,18,22], which does not allow the drawing of conclusions for European countries due to the different latitude.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, as social media and apps are widely used, their application in primary prevention campaigns may increase campaign efficacy, although this has yet to be investigated. These channels can be used to deliver and promote the most important messages (e.g., self-skin examination method) population-wide and may be prioritized in the near future [42][43][44].…”
Section: Discussionmentioning
confidence: 99%